(untitled) (Research, Society and Development, 2022)
Given the current pandemic context, the importance of adopting biosafety measures by different health professionals at all levels of care has been discussed. Thus, the objective of this study was to highlight and discuss, from the analysis of scientific productions already published, the biosafety measures adopted by different health professionals during the COVID-19 pandemic. This is an integrative literature review, whose searches were performed on the CAPES, BVS, SciELO and PubMed portal, through the combination of descriptors in English and Portuguese: “biosafety” AND “COVID-19” AND “health professionals”. The 16 selected studies were analyzed, summarized and tabulated to be discussed, based on the following categories: personal protective equipment (PPE), protocol and training, covering several areas of health. Personal protective equipment is an important measure for the safety of health professionals and patients, including face shields, surgical masks, N95/PFF2/PFF3 respirators, surgical gowns, gloves, cap and shoes. Protocols and recommendations related to Dentistry, Forensic Medicine, Audiology, Laboratory Biosafety and Home Environment have been developed. The policy of permanent education in health must be considered and used continuously.